Exploring nurses' experiences of value congruence and the perceived relationship with wellbeing and patient care and safety: a qualitative study. (March 2021) - Dunning, Alice; Louch, Gemma; Grange, Angela; Spilsbury, Karen; Johnson, Judith
Background: Values are of high importance to the nursing profession. Value congruence is the extent to which an individual's values align with the values of their organisation. Value congruence has important implications for job satisfaction. Aim: This study explored nurse values, value congruence and potential implications for individual nurses and organisations in terms of wellbeing and patient care and safety. Method: Fifteen nurses who worked in acute hospital settings within the UK participated in semi-structured telephone interviews. Thematic analysis was utilised to analyse the data. Results: Four themes were identified: organisational values incongruent with the work environment; personal and professional value alignment; nurse and supervisor values in conflict; nurses' values at odds with the work environment. Perceived value incongruence was related to poorer wellbeing, increased burnout and poorer perceived patient care and safety. The barriers identified for nurses being able to work in line with their values are described. Conclusions: Value congruence is important for nurse wellbeing and patient care and safety. Improving the alignment between the values that organisations state they hold, and the values implied by the work environment may help improve patient care and safety and support nurses in practice.